Earnings Management of Firms Reporting Material Internal Control Weaknesses under Section 404 of the Sarbanes-Oxley Act - Chan, Kam C.; Farrell, Barbara; Lee, Picheng (Auditing : a journal of practice and theory, 2008)
The main objectives of the Sarbanes-Oxley Act of 2002 are to improve the accuracy and reliability of corporate disclosure. Under Section 404 of the Sarbanes-Oxley Act, the external auditor has to report an assessment of the firm’s internal controls and attest to management’s assessment of the firm’s internal controls. Material weaknesses in internal controls must be disclosed in the auditor and management reports. The objective of this study is to examine if firms reporting material internal control weaknesses under Section 404 have more earnings management compared to other firms. The results provide mild evidence that there are more positive and absolute discretionary accruals for firms reporting material internal control weaknesses than for other firms. Since the findings of ineffective internal controls by auditors under Section 404 may cause firms to improve their internal controls, Section 404 has the potential benefits of reducing the opportunity of intentional and unintentional accounting errors and of improving the quality of reported earnings.